Effect of bacteriocin-producing Pediococcus acidilactici strains on the immune system and intestinal flora of normal mice - Yiteng Qiao; Zhichang Qiu; Fengwei Tian; Leilei Yu; Jianxin Zhao; Hao Zhang; Qixiao Zhai; Wei Chen (Food Science and Human Wellness)
This study was performed to determine the effects of bacteriocin-producing and non-bacteriocin-producing Pediococcus acidilactici strains on the immune system and intestinal flora of normal mice. Two P. acidilactici strains with antibacterial activity (P. acidilactici CCFM28 and CCFM18) were obtained based on the inhibition-zone assay. The produced components were identified as bacteriocins through protease treatment, pH adjustment and hydrogen peroxide treatment. Bacteriocin-producing and non-bacteriocin-producing P. acidilactici strains (P. acidilactici CCFM28, CCFM18 and NT17-3) caused significant changes in serum immune factors and intestinal flora of normal mice. After 14 days of intervention, the relative abundance of Firmicutes was significantly decreased, but that of Proteobacteria was significantly increased at the phylum level. At the genus level, the administration of three P. acidilactici strains resulted in the downregulation of Blautia and the upregulation of Ruminococcus and Lactobacillus. Furthermore, there were also different regulations on some probiotic strains, such as Bifidobacterium, Coprococcus and Akkermansia, which were closely related to the antibacterial ability of the bacteriocin and the type of strain. The results indicated that the intervention of different P. acidilactici strains could differently change the structure of intestinal flora in normal mice, which provided theoretical guidance for the selective use of bacteriocin-producing strains for health regulation in the future.